Appearance of calpain correlates with arthritis and cartilage destruction in collagen induced arthritic knee joints of mice. Issue 6 (June 1995) - Szomor, Z; Shimizu, K; Fujimori, Y; Yamamoto, S; Yamamuro, T
Abstract : OBJECTIVES--To determine the relevance of calpain in murine collagen induced arthritis (CIA) and to correlate the presence of m-calpain with the appearance of arthritis and cartilage destruction. METHODS--The immunohistochemical appearance and localisation of m-calpain at different stages of arthritis were analysed and compared with the histological changes occurring during type II CIA. The arthritic knee joint lavage was also examined for m-calpain by immunoelectrophoretic blotting. RESULTS--Immunohistochemical staining demonstrated a clear positive correlation between the appearance of m-calpain and both a histological grade of arthritis and an acute phase of cartilage destruction. Further development of the disease showed continual presence of m-calpain but with reduced intensity. Intra-articular inflammatory cells (mainly polymorphonuclear leucocytes, synovial lining cells, and sublining fibroblasts) were found to be the most positively stained, but extracellular localisation of m-calpain on the surface of cartilage and synovium, and in the articular cartilage matrix and chondrocyte lacunae, was also observed. In the knee joint lavage obtained at the most intensive stage of acute arthritis, m-calpain was detectable by immunoelectrophoretic blotting. CONCLUSIONS--The findings suggest that m-calpain may act at an early phase of CIA as a matrix proteinase and take part in the destruction of articular cartilage or activate other destructive enzymes.